Gamified pregnancy journey: enhancing fetal development education through interactive learning - Mohd Redzwan, Nur Lisa Najwa (2025)
The project, “Gamified Pregnancy Journey: Enhancing Fetal Development Education Through Interactive Learning”, primarily aims at bridging some of the gaps concerning maternal health education through gamification techniques in a mobile application called FetalFrames. It operates under three main objectives: (1) to identify the requirements that enhance information retention in expectant mothers regarding fetal development and pregnancy care; (2) to develop a mobile application incorporating gamified learning and quizzes to support expectant mothers in learning about fetal development and pregnancy care; and (3) to evaluate the effectiveness of gamified learning in improving users' understanding and reducing anxiety related to pregnancy. The mobile application was built using Android Studio (Java/XML) for frontend development and Firebase services (Authentication and Firestore Database) for backend operations. It implements a hybrid SDLC-Agile methodology which combines structured development with iterative user feedback-based enhancements. Early research and literature review provided the foundation for achieving the first objective by determining user needs such as interactive learning, personalized content, and consistent engagement. The second objective was realized through creating FetalFrames which is an Android mobile app that provides gamified experiences together with point-based rewards and weekly fetal development tracking features. The assessment of effectiveness for the third objective was based on System Usability Scale (SUS) results which showed that 100% of users found the navigation easy to use and 66.7% experienced lower pregnancy-related anxiety after interacting with the application. The average SUS score obtained from six users was 92.08, which falls under the “Excellent” usability category and is considered “Best Imaginable” on the SUS interpretation scale. FetalFrames provides special advantages to first-time mothers and patients with restricted healthcare access through its engaging and personalized educational content that is widely accessible. The application will undergo further development to support iOS platforms and multiple languages and offline functionality and AI-based personalization and healthcare professional collaboration for increased credibility and outreach. Through its combination of technology and gamification this project creates a new approach to maternal health education which delivers interactive learning experiences for healthier pregnancies.